Hallmarks of Cancer Dalam Aktivasi Invasi Jaringan dan Metastasis Melalui Persinyalan Adherens Junction - Prastiyo, Muhammad Dodik (Essential: Essence of Scientific Medical Journal, 2024)
Cancer is a global problem worldwide with high mortality rates. The process of cancer is studied more specifically in Hallmark of cancer. Hallmarks of cancer explains that there is one trait of cancer, namely tissue invasion and metastasis. The hallmarks of cancer  tissue invasion and metastasis is responsible for >90% of cancer deaths, so this article examines how the process of invasion and metastasis in cancer development.